Meningkatkan Niat Pembelian Ulang Pelanggan Horison Ultima Bekasi Melalui Sosial Media Marketing dan Persepsi Harga: Peran Intermediate Terhadap Kepuasan Pelanggan - MNA Mahartana; Bonifasius MH Nainggolan (Panorama Nusantara, 2022)
This study aims to analyze the impact of sociallmediaa marketingg, price perception on repurchase intentions through customer satisfaction. The population in this study consisted of guests who stayed at Horison Ultima Bekasi from January to April 2022. This study used a quantitative description method. This study uses important information obtained from appropriate opinion polls using purposive examination techniques. Data samples were collected from 109 guests who stayed at Horison Ultima Bekasi at least twice between January to April 2022. To test the proposed hypothesis, this study used the SEM-PLS (Partial Least Squares Structural Equation Modeling) approach. Partial least squares (PLS) analysis and evaluation was carried out in two steps. In the first step, reliability and validity analyzes were carried out, and in the second step, the path coefficients and explanatory power of the structural model were estimated and verified. This study uses SEM-PLS using SmartPLS 3.software. The results show that there is a direct positive+and significant+effect on sociall mediaa marketingg, price perception, and customer satisfaction with repurchase intentions. A Sociall mediaa marketingg and price perception also have a positive and significant+effect to customer satisfaction. The indirect effect of sociall mediaa marketingg does not affect repurchase intention at the expense of customer satisfaction. While the price perception has a positive+and significant+effect on the intention to repurchase through customer satisfaction, while the second stage evaluates and tests the path factors and explanatory power of the structural model.